PERANCANGAN MESIN POTONG AKRILIK YANG ERGONOMIS DAN EKONOMIS MENGGUNAKAN METODE ERGONOMIC FUNCTION DEPLOYMENT (EFD) - Huda Anshori (Jurnal Surya Teknika, 2020)
Advertising services which include the process of creating, producing and distributing advertisements, one example of which is billboards used to help entrepreneurs in promoting goods and services sold in Pekanbaru. In the process of working on advertising media, especially in the cutting process using cutting tools in the form of circular saws and scroll saws. In the cutting process there are several obstacles that are often experienced by operators, cutting edges are difficult to find, the unit is expensive, cutting edges often break, dynamo power can drop dramatically, work takes a long time and operators feel tired, that's why it is necessary to design an acrylic cutting machine which can be used to meet the operators needs at work. The design method uses the Ergonomic Function Deployment (EFD) method. This method is a development of the Quality Function Deployment (QFD) method. The stages in this research are introduction, identification, formulation, goal setting, method application followed by analysis and discussion, and finally conclusions, suggestions, and improvements. Based on the research, the variable results obtained from a closed questionnaire and processed using SPSS 16 software.